EVALUASI KAPASITAS ORGANISASI PADA UNIT PELAKSANA TEKNIS DAERAH LABORATORIUM LINGKUNGAN DI DINAS PERUMAHAN RAKYAT KAWASAN PERMUKIMAN DAN LINGKUNGAN HIDUP KABUPATEN TEMANGGUNG - Sulaswati, Sulaswati; Nugroho, Muhammad Awal Satrio (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2025)
This study aims to evaluate the organizational capacity of the Regional Technical Implementation Unit of the Environmental Laboratory at the Department of Public Housing for Settlement and Environmental Areas, Temanggung Regency. Research in December 2021. Types of qualitative descriptive research. Interview data collection techniques. Data analysis techniques Interactive Model of Analysis. The results showed that: 1) The organizational capacity of the Environmental Laboratory UPT DPRKPLH Temanggung Regency was not maximized. The contributing factors are: the limited number of environmental laboratory personnel, the competence of the UPT Environmental Laboratory DPRKPLH laboratory staff is still lacking, the infrastructure is inadequate, not supported by government policies, especially in terms of budget for tool calibration, proficiency testing, training/training makes the organization unable to develop. 2) Efforts are being made to increase organizational capacity, namely: submitting an application to the Regent through the Regional Personnel Agency (BKPSDM) for the recruitment of environmental laboratory officers, improving the skills, knowledge, abilities and competencies of laboratory officers with various relevant education and training. Increasing organizational capacity focuses on the management system following work procedures in the form of Method Work Instructions (IKM), improving laboratory infrastructure so that it is in accordance with IKM testing standards that refer to national and international standards, operating IKM tools, internal calibration IKM testing instruments and submitting budget requests for instrument calibration, proficiency testing and training.